Transfer Function Optimization for Band-Pass and Band-Stop Filters - Ayten, Tugba Saatci; Yildirim, Tulay (IEEE, 2019)
In this study, optimization of transfer functions of band-pass and band-stop filters are performed by using honey bee mating optimization and firefly optimization algorithms. In the conventional methods, the transfer functions of band-pass, band-stop and high-pass filters are obtained by means of frequency transformations using transfer functions of low pass filters. During this process, firstly, the transfer function approaching the ideal low-pass filter characteristic is obtained. Then with frequency conversion and frequency translation process; the transfer function is brought to the desired type and the desired frequency region. In this study, it is shown that transfer functions of band-pass and band-stop filters can be obtained by using evolutionary algorithms without frequency conversion.
Keywords: transfer function optimization; honey bee mating optimization; firefly optimization; evolutionary algorithms; band-pass filter; band-stop filter; Computer Science